2021
DOI: 10.1136/bmjmilitary-2020-001645
|View full text |Cite
|
Sign up to set email alerts
|

Role of sex and stature on the biomechanics of normal and loaded walking: implications for injury risk in the military

Abstract: Load carriage and marching ‘in-step’ are routine military activities associated with lower limb injury risk in service personnel. The fixed pace and stride length of marching typically vary from the preferred walking gait and may result in overstriding. Overstriding increases ground reaction forces and muscle forces. Women are more likely to overstride than men due to their shorter stature. These biomechanical responses to overstriding may be most pronounced when marching close to the preferred walk-to-run tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
(167 reference statements)
0
7
0
Order By: Relevance
“…The generally shorter heights of women has been suggested to increase their risk of stress fractures [ 46 ] however previous research in women is equivocal [ 47 , 48 ] and a positive association between height and stress fracture risk has been reported in men [ 49 ]. As advocated by Gill et al [ 50 ], further research is required that discerns sex and physical characteristics (e.g., anthropometric, strength, musculoskeletal loading) on biomechanical adaptation to load carriage and determinants of injury risk, and subsequent mitigation strategies, in military training.…”
Section: Discussionmentioning
confidence: 99%
“…The generally shorter heights of women has been suggested to increase their risk of stress fractures [ 46 ] however previous research in women is equivocal [ 47 , 48 ] and a positive association between height and stress fracture risk has been reported in men [ 49 ]. As advocated by Gill et al [ 50 ], further research is required that discerns sex and physical characteristics (e.g., anthropometric, strength, musculoskeletal loading) on biomechanical adaptation to load carriage and determinants of injury risk, and subsequent mitigation strategies, in military training.…”
Section: Discussionmentioning
confidence: 99%
“…Basic and career-long military training, unlike athletics, focuses on task-oriented performance that includes a multitude of environmental and physical stressors (Gold and Friedman, 2000) studies have reported sex differences in the response to military training with express concerns of how training can be optimized to prevent injury, especially in light of reports that by completion of basic training, 50% of females experience one or more injuries, including bone stress fractures, and are more likely to sustain injury when compared to males (Friedl et al, 2008;Gill et al, 2021). This may be due to a mixture of anatomical, biomechanical, and physiological differences between males and females.…”
Section: Sex Differences In Military Training Responsementioning
confidence: 99%
“…Whilst the physiological benefits of increased training load is desirable and support the use of weighted vests, the increased load carried could lead to increased risk of musculoskeletal injury (Wardle and Greeves 2017;Nindl et al 2016). Increased load carriage results in higher ground reaction forces during walking (Gill et al 2021) and running (Lobb et al 2019), with the higher impact affecting most of the ankle (increased load to push at the push-off phase) and the knee (during rebound after foot contact) joints (Huang and Kuo 2014) and this impact increases injury risk (Walsh and Low 2021). As the knee has been reported as one of the areas commonly injured in CrossFit V R training and the only lower-body site (Weisenthal et al 2014;Feito, Burrows, and Tabb 2018), the effects of load as a possible contributor to this statistic warrants investigation.…”
Section: Introductionmentioning
confidence: 99%
“…As the knee has been reported as one of the areas commonly injured in CrossFit V R training and the only lower-body site (Weisenthal et al 2014;Feito, Burrows, and Tabb 2018), the effects of load as a possible contributor to this statistic warrants investigation. Alteration in step length and cadence have been associated with injury risk during running, with decreased step length (Boyer and Derrick 2015) and associated increased cadence (Gerlach et al 2005) reported reducing the risk of running injuries likely via moderation of the increased impact induced by the additional load (Knapik, Harman, and Reynolds 1996;Gerlach et al 2005;Gill et al 2021). On the other hand, increases in both step length and cadence parallel to increased load during walking have been reported (Majumdar, Pal, and Majumdar, Sudan Pal, and Majumdar 2010). Step length and cadence, thus, were recorded for providing fundamental gait parameters as well as an indication of the injury risk associated with the additional load carriage (Park et al 2015;Schubert, Kempf, and Heiderscheit 2014).…”
Section: Introductionmentioning
confidence: 99%